2022
DOI: 10.3758/s13414-022-02608-x
|View full text |Cite
|
Sign up to set email alerts
|

Learning to suppress a distractor may not be unconscious

Abstract: The additional singleton task has become a popular paradigm to explore visual statistical learning and selective attention. In this task, participants are instructed to find a different-shaped target among a series of distractors as fast as possible. In some trials, the search display includes a singleton distractor with a different color, making search more difficult. This singleton distractor appears more often in one location than in the remaining locations. The typical results of these experiments show tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 51 publications
0
13
0
Order By: Relevance
“…Evidence suggests that these measures are unreliable and that most of the variability between one participant and another is simply measurement error (Vadillo et al, 2022). Simply including more participants and/or trials in the awareness test, or aggregating large samples of data through metaanalysis, is sufficient to show that participants are generally able to recognize the key statistical regularities embedded in the three tasks (Giménez-Fernández et al, 2020;Smyth & Shanks, 2008;Vadillo et al, 2016Vadillo et al, , 2020Vicente-Conesa et al, 2023).…”
Section: Unconsciousnessmentioning
confidence: 99%
“…Evidence suggests that these measures are unreliable and that most of the variability between one participant and another is simply measurement error (Vadillo et al, 2022). Simply including more participants and/or trials in the awareness test, or aggregating large samples of data through metaanalysis, is sufficient to show that participants are generally able to recognize the key statistical regularities embedded in the three tasks (Giménez-Fernández et al, 2020;Smyth & Shanks, 2008;Vadillo et al, 2016Vadillo et al, , 2020Vicente-Conesa et al, 2023).…”
Section: Unconsciousnessmentioning
confidence: 99%
“…Excluding these participants did not change the overall effect, t(133) = 2.58, p = .011, d = 0.22. Although this does not rule out the possibility that participants had some explicit knowledge regarding the underlying manipulation (Vadillo et al, 2020;Vicente-Conesa et al, 2022), it appears that the observed prioritization did not reflect a deliberate strategy but instead suggested implicit statistical learning.…”
Section: Experiments 1a and 1b: Awareness Of The Highprobability Targ...mentioning
confidence: 79%
“…Extracting regularities from the environment is one of the most fundamental abilities of any living organism and is often referred to as visual statistical learning (VSL; Chun & Jiang, 1998; Fiser & Aslin, 2001, 2002). Numerous studies have shown that the extraction of regularities via VSL can proceed without the intention to learn, and observers often appear to be unaware of the learning (Turk-Browne et al, 2005), although the extent to which learning is truly unconscious is debated (Vicente-Conesa et al, 2022).…”
mentioning
confidence: 99%
“…By using objective measures, many previous studies have claimed that the participants learn distractor regularities without their awareness in additional singleton search tasks (Failing, Feldmann-Wüstefeld, et al, 2019;Gao & Theeuwes, 2022;Wang & Theeuwes, 2018b). On contrary, by pointing out methodological shortcomings in previous studies, Vicente-Conesa et al (2022) with help of better measures of awareness (ranking and estimation methods) claimed that the participants were "aware" of distractor regularities (Vicente-Conesa et al, 2022). In any case, the relative contributions of whether the participants are "aware" or "unaware" of regularities on distractor suppression is not very clear (for review, see Theeuwes et al, 2022).…”
Section: Discussionmentioning
confidence: 97%